Lady of the Ministers of Tanukhiyya are scholars of hadith and jurisprudence - Assis.Lect. Najat Najeeb Hamid (Journal of College of Education, 2023)
Women participated in scientific life in all its fields and established a distinguished place for them in it because of the freedom they enjoyed in learning and teaching under the Islamic religion. They attended science and listening circles and contributed to spreading science and building schools and scientific houses. The star of many women shone high for their participation in attending councils and participating in scientific debates. In addition to the fact that their homes were scholarly gatherings, they left traces that reached us through their productions or through their male and female students or the manuscripts that reached us. Women scholars had a role in learning and transmitting the Prophetic hadith and Islamic jurisprudence. They later became a reference for many jurists and scholars.Based on this vision of women’s status, their scientific role continued throughout subsequent eras with the encouragement of their fathers or husbands. Ibn Hazm Al-Andalusi, the greatest scholar of Andalusia, mentioned his upbringing at the hands of women, saying: “I was raised in their laps, and grew up in their hands, and I did not know anyone else, nor did I sit with men except when I was in Young people...they taught me the Qur’an, recited many poems to me, and trained me in calligraphy.) This testimony is the best evidence that history is full of women scholars who had a great influence, and many famous men studied under their hands. They would travel in pursuit of knowledge, and students of knowledge from countries would travel to them. Other. The importance of some of them is that caliphs and kings would ask to consult them before making a decision, and some of them would even go to their councils to listen to their knowledge. Among them, Wazira bint Omar bin Asaad bin Al-Munji Al-Tanukhiyyah Al-Hanbaliyya emerged, whom we chose as the title of our research. She was nicknamed (the Lady of the Ministers), and Bin Taghri said about her. Bardi: (She became a traveler in her time, and people traveled to her from all over the world.) Many students were taught by her, including Judge Muhyiddin bin Fadlallah Al-Omari. Its translations and discussion of it were mentioned in several references, including “The Beginning and the End,” “Biographies of Noble Figures,” and “Arrangement of Notable Figures by Years
Keywords: Assis.Lect. Najat Najeeb Hamid